Women doctors in medicine - Pahor, Dušica (Acta Medico-Biotechnica, 2024)
According to Eurostat data, the gender ratio among physicians is changing in favour of women. In the year 2021, the share of women among doctors in Europe was 52.2%. The data refer to the 26 EU states for which data are available.